Current advances in ligand design for inorganic positron emission tomography tracers 68Ga, 64Cu, 89Zr and 44Sc. Issue 40 (11th February 2016) - Price, Thomas W.; Greenman, John; Stasiuk, Graeme J.
Abstract : A key part of the development of metal based Positron Emission Tomography probes is the chelation of the radiometal. Abstract : A key part of the development of metal based Positron Emission Tomography probes is the chelation of the radiometal. In this review the recent developments in the chelation of four positron emitting radiometals, 68 Ga, 64 Cu, 89 Zr and 44 Sc, are explored. The factors that effect the chelation of each radio metal and the ideal ligand system will be discussed with regards to high in vivo stability, complexation conditions, conjugation to targeting motifs and complexation kinetics. A series of cyclic, cross-bridged and acyclic ligands will be discussed, such as CP256 which forms stable complexes with 68 Ga under mild conditions and PCB-TE2A which has been shown to form a highly stable complex with 64 Cu. 89 Zr and 44 Sc have seen significant development in recent years with a number of chelates being applied to each metal – eight coordinate di-macrocyclic terephthalamide ligands were found to rapidly produce more stable complexes with 89 Zr than the widely used DFO.